Estratégias competitivas de marketing das empresas panificadoras de pequeno porte diante da concorrência: estudo de caso - Capibaribe, Dulce Eleonora Moreira (2006)
The competition today has many faces and it has persuaded all kinds of organizations to prepare for the unknown. To broaden your capacity for quick changes or come up with effective and creative initiatives became imperative. Therefore, the choice of strategy and the making of decisions can implicate in the survival of these companies. Our objective is to propose marketing strategies to be used by small bakeries, with a goal to obtain competitive advantages. We emphasize also the study of the strategies adopted by these companies, the comparison of these company’s strategic actions with the theories advocated by the referred authors and the evaluation of these actions in accordance with the company’s positioning. The themes of the theoretical referential that substantiated the field research along with the bakery’s businessmen and managers are associated to the following thematics: strategy and concepts, competitive advantages, strategic positioning and marketing strategy. The characteristics of the local bakeries and the profile of this sector were themes also studied for the better understanding on the subject. The researched companies are traditional bakeries and are of great economical importance for the region where they are installed. The research allowed us to confirm the unawareness of marketing. It was also verified, that the competition between companies of this sector is very aggressive, and that the companies which adopts marketing strategies do so with competitive advantages in mind. In a general way, it was observed that the elevated growth of the economy makes the changes in strategical behavior of the companies mandatory, which suggests a deeper look in to these questions.